Islam In South Thailand: Acculturation Of Islam In The Malay Culture - Suryadi Suryadi (FALASIFA : Jurnal Studi Keislaman, 2017)
In the perspective of history, the religious and cultural system of Patani Malays in Southern Thailand have underground evolution development stages from animism and dynamism to Hinduism and Buddhism. This ‘’old’’ culture has been handed down into the traditions and values as well as the mindset of the present day life and culture of the Patani Malays. The arrival of Islam has brought chnges in the religious and cultural system of the Patani Malays. The Patani’s worldview was formerly based on the religious and cultural system of animism, dynamism, Hinduism, and Buddhism in the term of their customs and traditions. This study examines the process of inculturation of Islamic values into Patani malay’s culture in Southern Thailand. This study used a descriptive-analytical method and an historical-anthropological approach. This study researches the Patani malay’s religious system and culture as manifested in their everyday life and the dynamic relationship of Islamic values and local culture. In so doing, the study can describe and analyze the development of Islamic Values and Patani Malay’s culture have eventually facilitated the process of its inculturation into Patani Malay’s religious system and culture.Keywords: The religious systems, Islamic values, culture, inculturation.